Adapting Self-Report Altruism Scale to Measure Altruistic Behavior of Pre-service Teachers in Indonesia - Suseno, Muchlas (International Journal of Psychosocial Rehabilitation, 2020)
Altruistic behavior is one among other personality traits that teachers should possess but it is difficult to resist a temptation not to ask if altruism can be measured. Such has been running for decades in long lasting debates and there a polar opposite conclusion still exists. This research was conducted to support those who claim there is a place that altruism can be measured. In particular this was directed to standardize a Self - Report Altruism (SRA) scale adapted from the original altruism measure of Rushton, Chrisjohn, and Fekken. The adaptation was essential to comply with the Indonesian context in the sphere of teaching profession and its validation was conducted in a five-step process, i.e. translating the scale followed by conceptual validation by a panel of judges, pilotting it out which involved limited respondents (N = 30). Following it, a standardization was made in which the instrument underwent several activities i.e. administered to bigger amount of respondents (N = 105), correlated with another measure of altruism (e.g. Carlo and Randall’s Prosocial Tendency Measure) to verify its concurrent validity (N = 51), then finally tested and retested for reliability assessment (N = 30). Data were collected from students of pre-service teacher program in English education. To standardize the adapted measure Exploratory Factor Analysis (EFA) was applied to ensure whether it yielded high internal consistency and if all items were extracted from the underlying attributive constructs. The research reveals the following results (1) all items are significantly inter-correlated which shows high internal consistency (r = .920), (2) one item was dropped out due to validity reason, (3) based on EFA 6 factors were extracted, (3) the concurrent validity is medium (r = 0.534), (4) the reliability coeficient after a 30-day-time interval showed high consistency (r = 0. 806). This means the adapted SRA scale is acceptable to measure altruistic behavior of Indonesian pre-service teachers.